If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(p-5)=27
We move all terms to the left:
3(p-5)-(27)=0
We multiply parentheses
3p-15-27=0
We add all the numbers together, and all the variables
3p-42=0
We move all terms containing p to the left, all other terms to the right
3p=42
p=42/3
p=14
| 7-5m+13=75 | | 2+5g+2g=-12 | | 5x=52= | | -2a-6+4a=18 | | x/(3x+16)=4/x | | (5y-13)=(9y+11) | | 7k-3k-4k+4k+1k=20 | | w=35.5/100 | | 5+6b-3=2+5b | | -3(j+70)=27 | | 3t+3.5=12.5 | | 7r+1=22 | | 2m=4806 | | 91=11-10c | | -2(q+37)=26 | | 14-2x=15-3x | | u-(-32)=70 | | 3(t+6)=2(t+8) | | 6b-6=36 | | 6b-6=3) | | 1.50b=9 | | 7q+6=27 | | 9(g+3)=54 | | 102=1.02*w | | 2x+6=4+2(x+1 | | 2(z-17)=66 | | 10q+10=30 | | 80=10(z+7) | | 7(u+7)=63 | | 3=b-54/8 | | 8x-7=61 | | 63=p+17 |